Characteristics of Gas Sensors Based on Co-Doped ZnO Nanorod Arrays. Issue 11 (2nd July 2020) - Chu, Yen-Lin; Young, Sheng-Joue; Ji, Liang-Wen; Chu, Tung-Te; Lam, Kin-Tak; Hsiao, Yu-Jen; Tang, I-Tseng; Kuo, Tzu-Hao
Abstract : In this investigation, gas sensors based on zinc oxide (ZnO) nanorods (NRs) with Co concentration were successfully fabricated and explored. A 100 nm-thick ZnO film was deposited as a seed layer onto Corning glass substrate via radio frequency (RF) magnetron sputtering technique. Then, Co-doped ZnO (CZO) NR arrays were grown by using a simple chemical bath deposition (CBD) method at 95 °C for 3 h and annealing at 450 °C, in which the Co-doping contents are 0, 5, and 10 mM. The surface-to-volume ratio of CZO NRs was higher than that of the pure ZnO structure. X-ray diffraction (XRD) results showed that the synthesised NRs were a single crystalline of the hexagonal wurtzite structure with uniform growth orientation of the c -axis. In addition, increasing ethanol (C2 H5 OH) response depends on O vacancy (VO ) adsorption, which is measured via photoluminescence (PL) emission. Compared with pure ZnO NRs, the results showed that the CZO-5 (with 5 mM Co solution) NRs exhibited a superior sensitivity in C2 H5 OH gas applications and a fast response/recovery time. Meanwhile, the CZO-5 gas sensor presented a high response rate of 90.71% at 300 °C operating temperature when the concentration of ambient C2 H5 OH gas was 100 ppm.